Readiness for Self-directed Learning among Nursing Students of Lumbini Medical College and Teaching Hospital: A Cross-sectional Study - Nepal, Parbati; Adhikari, Dipa (Journal of Lumbini Medical College, 2021)
Introduction: Self-directed learning is an independent learning approach and especially appropriate for adult learners where control over the learning is exerted by the learners than by teachers. Methods: A descriptive cross-sectional study was conducted among 147 nursing students. All the students of 2nd and 3rd years Proficiency Certificate Level (PCL) and 2nd, 3rd, and 4th-year bachelor in science (B.Sc) nursing were selected purposefully. The level of readiness was assessed through internationally validated “Self-Directed Learning Readiness Scale (SDLR)”. Data were analyzed using descriptive and inferential statistics. The p-value was set at <0.05. Results: The mean age of participants was 20.10±1.73 years and 55.1% of participants were from PCL nursing and 51.7% were from Brahmin/Chhetri ethnicity. Nearly three quarter (72.3%) were hosteller. A majority (83.7%) of participants had a high level of readiness for self-directed learning with an overall mean score of 158.78±14.27. The mean score (60.42±6.99) of self-control subscale was higher than the mean score of self-management (49.82±5.01) and desire for learning (48.53±5.47). The year of study (p<0.001), level of study (p<0.001), age (p<0.001), and grade obtained in previous level education (p<0.001) were statistically significant with the readiness level for self-directed learning. Conclusion: Nursing students had a higher level of readiness for self-directed learning, so the teachers need to adopt those learning strategies that help and encourage nursing students for independent learning which enhance student’s learning with better retention, good decision making, and confidence.